Surface modification of ion‐exchange membranes: Methods, characteristics, and performance. Issue 48 (25th August 2017) - Khoiruddin,; Ariono, Danu; Subagjo,; Wenten, I Gede
Abstract : Considerable effort has been made to improve ion‐exchange membrane (IEM) properties in order to achieve better performance of IEM‐based processes in various applications. Surface modification is one of the effective ways to improve IEM properties. Various methods have been used to modify IEM surfaces, for example, plasma treatment, polymerization, solution casting, electrodeposition, and ion implantation. These methods are able to produce a thin and fine distributed layer and also to modify the chemical structure of the surface. The new layer can be adsorbed, deposited, or chemically bonded on a membrane surface. By using these methods, IEM properties are improved, and the desired or specific characteristics such as high monovalent ion permselectivity, low fuel crossover, and anti‐organic‐fouling property can be obtained. In this paper, methods for surface modification of IEMs are reviewed. Moreover, the effects of modification on IEM properties and performance are discussed. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45540. Abstract :